The psychology of patriarchy in the scientific advancedIndian society: A study of MaheshDattani’sTara - Kumar, Tribhuwan (International Journal of Psychosocial Rehabilitation, 2020)
Mahesh Dattani’s drama Tara discusses issues of gender discrimination in society. In the present study, Dattani attempts to discuss and analyze how the play presents the marginalization of women. Through the story of twins, Tara and Chandan, Mahesh Dattani wants to tell how an Indian family likes a boy over a girl. Dattani considers gender discrimination unnatural and immoral and exposes the complex and multiple nature of the case. He portrays the play as a broad and deep integration of feminist values into the collective consciousness of society. These values are internalized by a process of socialization that makes women vulnerable to discrimination and oppression. Women work as a tool in the hands of masculinity to maintain feminine values. In the play, Tara’s mother ruins her daughter’s life and later suffers guilt due to her inhuman act. Their guilt leads them to insanity and also causes problems in the family. The play also touches the issue of gender-based labor and this section hinders the path of creativity and talent for both genders. She and Chandan are both different, but to be a girl, she has to suffer twice. Dattanihas thus highlighted the emotional attitude of the people towards the society. The play becomes more gruesome when one explores the misuse of science and technology through the character of Dr. Thakkar.